Optimizing Angkak Pigments and Lovastatin Production By Monascus purpureus - HASIM DANURI (Bogor Agricultural University, Indonesia, 2008)
Angkak pigments and lovastatin had been reported very useful as natural coloring agents, as an agent to increase thrombocyte level in Dengue hemorrhagic fever, and also as a compound that was able to control blood cholesterol level. Three strains of fungus Monascus purpureus AKI, AKII, and 915 were selected to produce angkak pigments and lovastatin in potato dextrose agar (PDA) medium. The best fungus strain, which is AKII, was then applied in three kinds of rice media (white rice IR-42, red rice BP-1804-IF-9, and a combination of 1:1 (w/w) white IR-42 and red rice BP-1804-IF-9 for solid fermentation. The best medium and fermentation times were determined for the production of angkak pigments and lovastatin separately. Results showed that strains, media, and duration of fermentations gave significant effect on the amount of pigment produced. Strain AKII produced highest concentration of angkak pigments. The combination of rice (White IR-42 and red rice BP-1804-IF-9) produced the highest pigment than the individual white and red rie it self. The optimum duration of fermentation was 16 days for strains AKI and AKII, but only 15 days for strain 915. Therefore the strain AKII with media combination of rice and a fermentation time of 16 days were used to investigate the additional effect of various minerals. Addition of the mineral individually gave significant increased on angkak pigment production by AKII, where as the addition of minerals mixture in the forth tube did not. Key words: angkak, pigments, lovastatin, monascus purpureus